Circular RNAs as Biomarkers in Breast Cancer Diagnosis, Prognosis, Molecular Types, Metastasis and Drug Resistance - Li-Xin Li BM; Yun Hao BM; Lei Dong BM; Zhong-Qi Qiao BM; Shun-Chao Yang BM; Yan-Duo Chen MM; Kai Zhang MD; Ya-Wen Wang MD (Technology in Cancer Research & Treatment, 2025)
Breast cancer is one of the leading causes of cancer-related deaths in women worldwide. Circular RNAs (circRNAs), a novel class of endogenous noncoding RNA with a covalently closed continuous loop that lacks the 5′-cap structure and the 3′-poly A tail, are more stable than linear RNAs and less susceptible to degradation by nucleases. CircRNAs are widespread in multiple mammalian genomes and have been detected in various tissues, cells and body fluids. Increasing evidence shows that abnormal expression of circRNAs is involved in the development of a variety of diseases, including breast cancer. Numerous studies have explored the potential of circRNAs as biomarkers in various malignant tumors. In this review, we aim to provide a comprehensive overview of the latest advances in circRNAs as promising biomarkers in the early diagnosis, prognosis, molecular type, metastasis and drug resistance of breast cancer.